2019
DOI: 10.4269/ajtmh.18-0656
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based Survey on Health-Care Utilization for Pneumonia in Children in Peri-Urban Slums of Karachi, Pakistan

Abstract: Abstract.Pneumonia, as defined by WHO, is a syndromic diagnosis characterized by presence of cough or difficult breathing. Presentation to health-care provider depends on timely identification of signs and symptoms by caretakers. We explored patterns of health-care utilization among caretakers of a randomly selected sample of 1,152 children aged 2–59 months, residing in low-income settlements of Karachi, Pakistan. Information on household demographics, occurrence of pneumonia-specific symptoms, care seeking, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Personal and biological factors: The common factors associated with healthcare accessing and utilisation included intrinsic factors such as age,21 39–55 sex18 21 41 45 51 53 55–58 and ethnicity,21 familial factors such as birth order of the sick child,21 46 59–61 as well as personal health and type of illness,45 58 disability47 and morbidity,21 51 62 63 and the specific features of the health condition 52 55 64. Slum residents are more likely to seek healthcare services when sick children are younger,48 49 52 55 but evidence on the association between mother’s age and child’s vaccination was inconsistent 21 39. Healthcare seeking and utilisation were different by sex, but the association was context dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Personal and biological factors: The common factors associated with healthcare accessing and utilisation included intrinsic factors such as age,21 39–55 sex18 21 41 45 51 53 55–58 and ethnicity,21 familial factors such as birth order of the sick child,21 46 59–61 as well as personal health and type of illness,45 58 disability47 and morbidity,21 51 62 63 and the specific features of the health condition 52 55 64. Slum residents are more likely to seek healthcare services when sick children are younger,48 49 52 55 but evidence on the association between mother’s age and child’s vaccination was inconsistent 21 39. Healthcare seeking and utilisation were different by sex, but the association was context dependent.…”
Section: Resultsmentioning
confidence: 99%
“…This limited public sector service delivery in slums leaves a vacuum that has been filled by the private sector. Research shows, and respondents confirmed, that many slum dwellers are increasingly seeking care from the private sector, including unregistered healthcare providers, traditional healers, “quacks”, and drug sellers [ 38 ]. As private sector care is usually more expensive, slum populations are reportedly spending an increasing percentage of their incomes on out-of-pocket medical costs (Participant 6, personal communication, January 25, 2016) [ 1 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The impact of paternal education could be due to the cultural practice that exists in Pakistan, where fathers are deemed decision makers in households and influence health-seeking behaviors, nutrition, and general living conditions of the family, which directly impact childhood morbidities ( 22 , 23 ). A recently conducted study in Pakistan concluded that education of caretakers can improve the recognition of danger signs in children and consequently improve care-seeking practices ( 24 ).…”
Section: Discussionmentioning
confidence: 99%